La Familia en la educación sexual de los Niños y Niñas de los 5tos a 7mos Años de la Escuela de Educación Básica Alonso de Mercadillo de la Ciudad de Loja, y la intervención del Trabajador Social - Jiménez Quevedo, Carina Alexandra (2018)
This research work entitled “THE FAMILY IN THE SEXUAL EDUCATION OF CHILDREN FROM THE 5TH TO THE 7TH YEARS OF THE BASIC EDUCATION SCHOOL ALONSO DE MERCADILLO OF THE CITY OF LOJA, AND THE INTERVENTION OF THE SOCIAL WORKER” refers to sex education as an aspect of the life of the human being that must be approached from the first years of life and in which the family should be the basis for this process; in this context, the present research work was planted as a scientific question. How does the family affect the sexual education of children from the fifth to seventh years of the the basic education school Alonso de Mercadillo? The aim of the research is to improve the participation of the family in the sexual education of the children of the institution for which it is necessary to make the scientific basis of the categories of analysis. Through the methodology used it was possible to establish the factors that determine the incidence of the family on the object of study and based on the results obtained in the investigative process an intervention proposal was proposed from the perspective of social work that involves participation of the educational community. The methodology used was based on the scientific, deductive, inductive, analytical and synthetic methods, through the use of research instruments such as the survey and the interview that were applied to the sample delimited in 11 members of the 6 teaching staff, 45 parents. and 45 students of the fifth to seventh parallel years A, B, and C of the basic education school Alonso de Mercadillo of the city of Loja; which were selected through random probabilistic sampling and based on non-pro-ballistic-causal sampling. The results found are: 76% of the students indicated that in their family they had NOT been told about sexuality, with respect to the parents 53% stated as Sometimes the frequency with which they talk with their son or daughter about sexuality, which shows that the participation of the family in the sexual education of boys and girls is an aspect that is being left aside mainly for issues related to shame for not knowing the appropriate terms to sexually educate the boy or girl. Misinformation on sexuality issues that should be addressed at this stage of childhood as well as lack of time due to the work of parents is the cause of the existing problem. The results obtained merit a proposal of social intervention with the purpose of improving the participation of the family in the sexual education of boys and girls, which must involve the participation of the educational triad: teachers, parents and students, and so on. To fulfill the general objective of the research: "To improve the participation of the family in the sexual education of the children of the basic education school Alonso de Mercadillo through a proposal of social action".